2015
DOI: 10.3923/ijds.2015.160.172
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Ice Cream Containing Cress Seed and Flaxseed Mucilages Compared with Commercial Guar Gum

Abstract: The effect of using ethanol precipitated cress seed (CSM) and flaxseed (FSM) mucilages in ice cream manufacture compared with commercial Guar Gum (GG) was studied. Ten treatments of ice cream mixes consisted of 10.0% milk fat, 11.5% MSNF and 15.0% sucrose were prepared. The CSM, FSM and GG were added separately at the rates of 0.025, 0.05 and 0.10% (w/w) to create 9 treatments. The latter batch had no polysaccharides' serve as a control. The results showed that the using of CSM and FSM had no significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
3
7
1
Order By: Relevance
“…The melting rate results unlike those determined by El‐Aziz et al. (2015) and Chavan et al. (2017).…”
Section: Resultscontrasting
confidence: 81%
“…The melting rate results unlike those determined by El‐Aziz et al. (2015) and Chavan et al. (2017).…”
Section: Resultscontrasting
confidence: 81%
“…These may be due to antimicrobial activity of (WSELP) as reported by (Adelani et al, 2015). These results are in agreement with Abd El-Aziz et al (2015), who produced ice cream supplemented with cress seed and flaxseed mucilage.…”
Section: Nutritional Value and Chemical Composition Of Ice Milk Supplemented With Water Melon Seeds Embryonic Leaves Powdersupporting
confidence: 92%
“…The apparent viscosity provided behavioural changes in the overrun because by increasing the concentration of variables x 1 and x 3 , a thickening of the mix could be observed, causing difficulties to the air incorporation during stirring and freezing; this prevented the formation and stabilisation of the air cells. Similar results were described by El-Aziz et al (2015) and Javidi et al (2016); when using a combination of different hydrocolloids, they reported a reduction in the percentage of overrun due to increased apparent viscosity of mix, since the concentrations of these gums were increased. In tests with lower values of LBG and BMT (Table 2), even in association with CM (T1 and T5), the volume increase of the frozen dessert was outstanding.…”
Section: Overrunsupporting
confidence: 84%
“…Hydrocolloids from grains have been reported in studies about frozen dessert. Campos et al (2016), Javidi et al (2016) and El-Aziz et al (2015) used chia mucilage, basil gum and flaxseed gum, respectively. Chia grains (Salvia hispanica L.) have been authorized for use as ingredient in foodstuff through Commission Decision 2009/827/EC (European Communities, 2009).…”
Section: Introductionmentioning
confidence: 99%